Analysis of the Impact of Globalization, Digital Technology, and Socio-Cultural Change on Community Identity in the Modern Era in Jakarta - Judijanto, Loso; Ardianto, Rian; Soegiarto, Ita (Westscience Press, 2023)
This research explores the intricate interplay between globalization, digital technology, socio-cultural changes, and community identity in Jakarta, utilizing a quantitative approach. The study, based on a sample of 150 participants, employs structural equation modeling to analyze the relationships among these constructs. Descriptive statistics reveal a diverse demographic profile, while the measurement model ensures the reliability and validity of the chosen variables. The structural model elucidates significant positive relationships: digital technology, globalization, and socio-cultural changes positively influence community identity. Demographic nuances, such as age, gender, and socio-economic status, further shape these dynamics. The findings contribute to understanding community dynamics in the modern era and provide valuable insights for policymakers and community leaders.